Note - Maria Teresa Lucarelli (TECHNE - Journal of Technology for Architecture and Environment, 2020)
The theme that this issue proposes is undoubtedly of great suggestion; equally undeniable is that it is a subject of many facets and complexity not only because of the different definitions and interpretations that have been given to “time” since ancient times, but also because of its relationship with architecture that is appropriated and nourished by time. As can be seen from the contributions of the Dossier, which introduces the essays and research presented here, many distinguished scholars – architects, philosophers and intellectuals – have tried their hand at investigating this relationship, developing, in the specificity of their thought, interesting critical reflections that focus on the aspect of memory, continuity and/or change, declining in a harmonious way the concept of permanence, «[…] included in the continuous and changeable flow of becoming» (Truppi, 2012), with that of temporariness intended not only as a solution to the emergency but as attention to the varied housing needs of a society in constant change, a strategic design option in which attention to flexibility, in the articulation of spaces and reversibility, in the definition of uses can allow for greater durability over time.